Prevalence of early childhood caries in South Africa: a systematic review - Faheema Kimmie-Dhansay; Robert Barrie; Sudeshni Naidoo; Tina Roberts (BMC, 2022)
Abstract Background The prevalence of Early Childhood Caries (ECC) in South Africa was last determined in 2002 in a national survey. Since then only few scattered studies were conducted across pocketed communities in the country. There appears to be an increasing trend in dental caries prevalence in South Africa. Since South Africa has one of the highest burden of HIV in the world, less focus was spent on Non-Communicable Diseases (NCDs), it was only when HIV patients developed NCD's did the government start evaluating NCDs. However, oral health is still not given enough attention within the health sphere. It is the hope of this systematic review to showcase the extent of dental caries amongst the future leaders of our country. Objectives The systematic review presents the prevalence and severity of early childhood caries between age groups and provinces in South Africa from 1975 to 2014. Design A systematic review of prevalence was performed. Settings and participants: All studies performed on children under the age of six who lived in South Africa were eligible to be included. Primary and Secondary outcome measures The prevalence of ECC and the dmft scores were the primary and secondary outcome measures. Results Twenty-one studies were included in the present review. The overall prevalence was 44.94% (95% confidence interval (C.I.) 39.73-50.15%) and the overall dmft score was 2.422 (95% C.I. 2.148-2.696). Conclusions The dmft score was the lowest in the Limpopo Province and highest in the Eastern Cape. ECC prevalence increased post-apartheid possibly on account of lifestyle changes due to the exodus from rural to urban and peri-urban areas. Registration The protocol of this systematic review was registered with PROSPERO, CRD42018112161, in November 2018.